Adverse childhood experiences in patients with schizophrenia: related factors and clinical implications - Zhang, Lei; Zhao, Nan; Zhu, Minghuan; Tang, Minyi; Liu, Weiqing; Hong, Wenjuan (Frontiers in Psychiatry, 2023)
The relationship between adverse childhood experiences (ACEs) and the development of psychotic symptoms is not well understood. Therefore, this study aimed to investigate the frequency and distribution of ACEs among patients with schizophrenia and their potential correlation with symptomatology and personality pathology. We conducted a cross-sectional study involving 571 patients with schizophrenia in Shanghai, China. Symptomatology was assessed using the Positive and Negative Symptoms Scale (PANSS) and personality pathology was assessed using the Personality Diagnostic Questionnaire Fourth Edition Plus (PDQ-4+). ACEs were assessed using the Child Trauma Questionnaire-Short Form (CTQ-SF). ACEs were highly prevalent, with 80.8% of the patients with schizophrenia reporting at least one ACE. The three most common types of ACE were physical neglect (69.8%), emotional neglect (28.2%), and emotional abuse (22.9%). For specific ACE, emotional abuse was significantly associated with PD traits, whereas emotional and physical neglect types of ACE was significantly associated with negative symptoms. A higher level of physical abuse was more commonly reported by men, younger individuals, and those with a higher level of antisocial PD traits. Higher levels of physical neglect were associated with more severe negative symptoms. ACEs are commonly observed in patients with schizophrenia. Therefore, it is strongly recommended that this clinical population be provided with a comprehensive assessment and individualized intervention for those exposed to specific ACEs.